Figure-of-eight bandage versus arm sling for treating middle-third clavicle fractures in adults: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Lenza, Mario; Taniguchi, Luiz; Ferretti, Mario
Abstract Background Fracture of the clavicle is common, accounting for 2.6 to 4.0 % of all fractures, with an overall incidence of 36.5 to 64 per 100, 000 per year. Around 80 % of clavicle fractures occur in the middle third of the clavicle. Randomised controlled trials comparing treatment interventions have failed to indicate the best therapeutic practices for these fractures. The objective of this study is to evaluate the effects (benefits and harms) of two commonly-used conservative interventions: the figure-of-eight bandage versus the arm sling as treatments of middle-third clavicle fractures. Methods/design This project has been designed as a single-centre, two-arm randomised controlled trial that will compare two interventions: figure-of-eight bandage versus the arm sling. We propose to recruit 110 adults, aged 18 years or older, with an acute (less than 10 days since injury) middle-third clavicle fracture. The primary outcomes to be evaluated will be function and/or disability measured by the Disability of the Arm, Shoulder, and Hand (DASH) questionnaire. In order to assess the secondary outcomes, the Modified University of California at Los Angeles (modified – UCLA) Shoulder Rating Scale will be used. The occurrence of pain (Visual Analogue Scale for pain (VAS)), treatment failure, adverse events and the ability to return to previous activities will also be recorded and evaluated as secondary outcomes. Data analysis: the primary outcome DASH score and the secondary outcomes – modified UCLA and VAS scores – will be analysed graphically. We will apply generalised mixed models with the intervention groups (two levels), and time-point assessments (seven levels) as fixed effects and patients as a random effect. Discussion According to the current literature there is very limited evidence from two small trials regarding the effectiveness of different methods of conservative interventions for treating clavicle fractures. This is the first randomised controlled trial comparing the figure-of-eight bandage versus the arm sling for treating clavicle fractures that follows the CONSORT Statement guidelines. Trial registration ClinicalTrials.govNCT02398006 .